Effect of Pedagogical Competence and Work Motivation on the Performance of Educators in SMP Muhammadiyah 4 Gempol: Pengaruh Kompetensi Pedagogik dan Motivasi Kerja terhadap Kinerja Pendidik di SMP Muhammadiyah 4 Gempol - Hanim, Faridah; Nurdyansyah, Nurdyansyah; Ruchana, Siti (Proceedings of The ICECRS, 2020)
Educators determine the success of an education because they are as central figure in learning. Educators who have good pedagogical competence will be able to understand what is needed and desired by students in the learning process. Therefore, educators are required to improve the quality and the performance of education. This study aims to determine the effect of pedagogical competence on teacher performance, the effect of work motivation on teacher performance, and the influence of pedagogical competence and work motivation on teaher performance in Muhammadiyah Junior High School 4 Gempol. This type of research is quatitative research methods. In this study the data collection techniques used are, interview techniques and documentation techniques. The results of this study are that if educators have good pedagogical competence and high work motivation, then the performance of educators will be optimized in a comprehensive manner and more quickly achieved in improving the quality of education. And vice versa, if educators do not have poor pedagogical competence and low work motivatoin, the teacher's performance is said to be poor or not qualified.